2019
DOI: 10.1099/jgv.0.001209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fowlpox virus in chickens and bird-biting mosquitoes: a molecular approach to investigating Avipoxvirus transmission

Abstract: Avian pox is a highly contagious avian disease, yet relatively little is known about the epidemiology and transmission of Avipoxviruses. Using a molecular approach, we report evidence for a potential link between birds and field-caught mosquitoes in the transmission of Fowlpox virus (FWPV) in Singapore. Comparison of fpv167 (P4b), fpv126 (VLTF-1), fpv175–176 (A11R-A12L) and fpv140 (H3L) gene sequences revealed close relatedness between FWPV strains obtained from cutaneous lesions of a chicken and four pools of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
0
18
1
Order By: Relevance
“…Amplicons generated by avian and mammalian PCR on each pool were subjected to sequencing to determine the host species/genus. These primers have been designed to avoid/minimize annealing to mosquito DNA and have been validated in numerous avian and mammalian species (Kek et al 2014, Yeo et al 2019. Mosquito pools were assayed in a reaction mixture (20 lL) containing 1 • PhusionÔ Flash High-Fidelity PCR Master Mix (Thermo Scientific, Inc., USA), 0.5 lM of forward and reverse primers, and 2 lL of template DNA.…”
Section: Bloodmeal Identificationmentioning
confidence: 99%
“…Amplicons generated by avian and mammalian PCR on each pool were subjected to sequencing to determine the host species/genus. These primers have been designed to avoid/minimize annealing to mosquito DNA and have been validated in numerous avian and mammalian species (Kek et al 2014, Yeo et al 2019. Mosquito pools were assayed in a reaction mixture (20 lL) containing 1 • PhusionÔ Flash High-Fidelity PCR Master Mix (Thermo Scientific, Inc., USA), 0.5 lM of forward and reverse primers, and 2 lL of template DNA.…”
Section: Bloodmeal Identificationmentioning
confidence: 99%
“…We noticed moderately high Wolbachia infection in Culex quinquefasciatus which is a member of the Culex pipiens complex responsible for the transmission of lariasis worm disease in Singapore [87,88]. Surprisingly, between closely-related species, Culex pseudovishnui and Culex vishnui [96], we only found high percentage infection in the former. However, previous studies in India and Thailand showed a reverse pattern -infection in Cx.…”
Section: Discussionmentioning
confidence: 59%
“…We noticed moderately high Wolbachia infection in Culex quinquefasciatus (62.5%) which is a member of the Culex pipiens complex responsible for the transmission of lariasis worm disease in Singapore [86,87]. Surprisingly, between two closely related species, Culex pseudovishnui and Culex vishnui [88], no Wolbachia infection was observed in the latter which has been found to harbour Japanese encephalitis virus in the Southeast Asian region [89]. However, studies in India and Thailand showed a reverse pattern, with Wolbachia infection present in Cx.…”
Section: Detection Of Wolbachia Infection and Distribution In Wild Momentioning
confidence: 82%